The Digital City Tour Guide Using Augmented Reality on the Pasupati Bridge: City Tour Guide Digital Menggunakan Augmented Reality Pada Jembatan Pasupati - Rhomadiniyah, Dewi; Dijaya, Rohman; Rahmawati, Yunianita (Procedia of Engineering and Life Science, 2023)
Bandung is a must-visit tourist destination, including those around the Paupati Bridge. The Pasupati Flyover or Pasupati Bridge is an icon of Bandung City. Because of its cool and original location, there is also an ancient building making Bandung interesting to visit and be introduced to its tourism field. One method for propelling the travel industry is with special media. By using Increased Reality (AR)- based data innovation, it can show 3D virtual articles into a genuine climate and construct 3D picture representations. AR can be utilized as an option limited time medium that assists clients with getting more clear data about the fascination they need to visit. This research aims to promote tourism with Augmented Reality using the Multimedia Development Life Cycle (MDLC) Method. The results of this study are Information and 3D images of tourism in which there is a 3D import feature to include images. It can contribute to helping tourists search for information about tourism in an area.